Analisis Thibaq dalam Surah al-Ahzab - Nurdin, Aldi; Komarudin, Edi; Taufik, Wildan (Jurnal Penelitian Ilmu Ushuluddin, 2024)
This research aims to reveal and analyze the phenomenon of Thibaq contained in Surah al-Ahzab and to decipher the meaning of the verses contained in Thibaq. This research is a type of qualitative research with data collection techniques based on literature study. The research results show that there are two types of Thibaq in surah al-Ahzab, namely Thibaq ijab and Thibaq salb, where Thibaq ijab is found in 7 verses while Thibaq salb is found in 1 verse. In surah al-Ahzab there are 8 verses that contain Thibaq elements.